The relationship between the atherosclerotic cardiovascular disease risk score used in the prediction of cardiovascular disease risk and endocan. - Cakirca, M; ÇAKIRCA, MUSTAFA; Tunc, M; Zorlu, M; ZORLU, MEHMET; Dae, SA; Kiskac, M; TUNÇ, MUHAMMED; Karatoprak, CUMALİ; KARATOPRAK, CUMALİ (My University, 2019)
Objective: To date, there have been no studies investigating whether or not there is a correlation between the serum endocan level and the atherosclerotic cardiovascular disease (ASCVD) risk score that is frequently used in the determination of the risk of cardiovascular disease. If a single parameter such as endocan can provide reliable results which could be used in the prediction of the cardiovascular disease risk, the workload of the clinician would be lightened. The aim of this study was to investigate whether or not there is an association between the serum endocan level and the ASVCD risk score. Materials and methods: This prospective, cross-sectional study included individuals age 40-79 years with risk factors calculated using the ASVCD score and individuals without any of those risk factors. In accordance with ASCVD risk calculation, each participant was questioned with respect to age, gender, height, weight, and lifestyle habits such as smoking, diseases, and medications. Systolic blood pressure, diastolic blood pressure, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and serum endocan levels were measured and recorded. The serum endocan levels and ASCVD scores were compared. Results: The study included 205 individuals, comprising 92 (44.9%) males and 113 (55.1%) females with a mean age of 50.7 ± 7.6 years. The 10-year atherosclerosis risk was determined as mean 6.32% ± 5.9% (range, 0.3%-27.3%). The mean serum endocan level was calculated as 1109.6 ± 1479.7 ng/mL. As the ASCVD risk score increased, no increase was detected in the serum endocan level. Conclusion: The results of the study suggested that the serum endocan level is not suitable for use in place of the ASCVD risk score as a predictor of cardiovascular disease risk.
Keywords: Atherosclerotic cardiovascular disease risk score; atherosclerosis; cardiovascular disease; endocan